Effect of vanadium on calcium homeostasis, osteopontin mRNA expression, and bone microarchitecture in diabetic rats. Issue 3 (14th February 2017) - Sanchez-Gonzalez, Cristina; Moreno, Laura; Lopez-Chaves, Carlos; Nebot, Elena; Pietschmann, Peter; Rodriguez-Nogales, Alba; Galvez, Julio; Montes-Bayon, María; Sanz-Medel, Alfredo; Llopis, Juan
Abstract : The aim was to examine whether alterations caused by diabetes in calcium homeostasis, expression of osteopontin and the microarchitecture of bone are corrected by vanadium. Abstract : The aim of this study was to examine whether alterations caused by diabetes in calcium homeostasis, expression of osteopontin and the microarchitecture of bone are corrected by exposure to vanadium. Four study groups were examined over a period of five weeks: control (C), diabetic (DM), diabetic treated with 1 mg V per d (DMV), and diabetic treated with 3 mg V per d (DMVH). Vanadium was supplied in drinking water as bis(maltolato)oxovanadium(iv ). Calcium was measured in the food, faeces, urine, serum, kidneys, liver, muscles, and femur. Osteopontin gene expression was determined in the liver, and the bone microarchitecture was studied with the aid of micro-computed tomography. In the DM group, food intake as well as calcium absorbed and retained and liver osteopontin mRNA increased, while Ca in the serum and femur decreased, and the bone microarchitecture worsened, in comparison with the control. In the DMV group, the amount of Ca absorbed and retained was similar to DM rats. Although the Ca content in the femur increased and osteopontin mRNA decreased, there were no significant changes in the bone microarchitecture, in comparison to the DM rats. In the DMVH group, the amount of Ca absorbed and retained, and the serum and femur content were equivalent to the control. The levels of osteopontin mRNA decreased and bone mineralization improved, compared to the DM group. We conclude that treatment with 3 mg V per d of the glucose lowering agent bis(maltolato)oxovanadium(iv ) causes a decrease in osteopontin mRNA, which could favour the normalization of changes in Ca homeostasis and bone microarchitecture, both at the cortical and trabecular levels, caused by diabetes.